8 - Potentialising Traditional Peacebuilding System towards Resolution of Land Disputes in African communities - Lamidi, Kazeem Oyedele (Africa Development, 2024)
Land is a common cause of conflict in Africa. It is at the root of much social unrest and violence among family members, groups and communities. Although the state judicial system has been a major adjudicator in these instances, their case pronouncements have brought little or no recourse to peaceful co-existence among the conflicted parties. This article seeks to advance the potential of the traditional peacebuilding system as a ‘community friendly’ option especially for constructive land dispute resolution. Traditional peacebuilding is devoid of long judicial proceedings, ‘preconceived’ justice and high costs. This article argues that, unlike the state judicial system, traditional peacebuilding is not only about making resolutions through rational choice, custom knowledge, community history and social cohesion but also about enhancing restorative justice, inclusiveness and peace promotion, and developing the trust and safety that is so badly needed across African communities. It, therefore, concludes that the traditional peacebuilding system has an organisational propensity to resolve land disputes within an institutionalised structure across African communities.